CUBE Enterprise / Nurul Afiqah Ismail... [et. al]. - Ismail, Nurul Afiqah; Saharuddin, Nur Azlin; Md Shukor, Siti Suhailah; Mohamad Mustafa, Azua Amira (2012)
This business is based on partnership where it consists of four (4) members. The members consist of the General Manager cum Administration Manager, Marketing Manager, Operational Manager and Financial Manager. The business capital is amounted to RM 50, 602. We also take loan from bank amounted to RM 75,000. CUBE Enterprise is a company related to the sweet corn based product. Our market focus is to introduce a new style of healthy fast-food to the public. The uniqueness of our product is it has variety of flavor, friendly-use container, and been accompanied with several types of toppings. Our business will be expected to commence on January 2013 and our vision is to make our company a well-known producers of healthy fast-food that satisfied our worldwide customer. This will be realized by the full cooperation and efforts among the partners to promote this company. Based on the objectives above, we are venturing into the fast-food industry. Healthy fast-food has the potential of being a profitable business if it's done in modern and unique way that may attract customer at different age or gender. We will expect that our business will become more developed in the near future because the demand for the healthy fast-food is high and yet now this kind of business is started to grow. This will give more advantages for us to make our product more profitable and stabile in the long run.